Empirical study: Is there Speculative Bubble in Chinese Stock Market? - Song, Zhiyun (2007)
The paper starts from the two stock market debate in the Chinese stock market,concerning whether there is speculative bubble in the stock market in 2001 and 2007. By examining both Shanghai A share index and Shenzhen composite index based on the deterministic bubble model, we found the there is no speculative bubble in the market during 1999 to 2005, whereas the bubble does existing in the current market.To verify the results, the paper further looked at the activities in the market, finally come with the conclusive answer -- there is bubble in the current market, though the significance of the bubble is unknown. In addition the paper also looked at the possible causes of speculative bubble and relevant policy recommendations are given.